Association between serum magnesium and obesity in postmenopausal women - Yadav, Alka; Gupta, Madhuri; Gupta, R. C. (International Journal of Research in Medical Sciences, 2018)
Background: Obesity is a complex, multifactorial condition in which excess body weight may put a female at risk of serious health problems such as hypertension, dyslipidemia, diabetes mellitus and cardiovascular diseases. Magnesium deficiency is reported to be associated with obesity in children and adolescents. An inverse relationship has been reported between serum magnesium and estrogen levels in women. It is not known whether magnesium deficiency may have a role in genesis of obesity in women after menopause. Therefore, the present study was planned to compare serum magnesium levels in obese and non-obese postmenopausal women and to find out the relationship, if any, between serum magnesium levels and obesity. Methods: This cross-sectional study was conducted in the department of Biochemistry at National Institute of Medical Sciences and Research, Jaipur, Rajasthan on fifty subjects over a period of six months. Twenty-five obese postmenopausal women (BMI ≥ 30) having their final menstrual period at least one year prior to the study were taken as the study group and twenty-five non-obese (BMI ≤ 22.9) post-menopausal women were taken as control group. All subjects were asked to give detailed dietary history using Food Frequency Questionnaire (FFQ). Venous blood samples were collected after an overnight fast for estimation of serum total magnesium in all subjects. Results: Obese postmenopausal women had significantly higher weight (78.36±0.064kg) and BMI (32.68±1.7kg/mt2) compared to non-obese postmenopausal women (wt. 54.72±4.80kg and BMI 21.75±1.68kg/mt2). The mean±SD serum magnesium concentration found in the obese postmenopausal women was 1.40±0.45mg/dl as compared to 2.03±0.49 mg/dl in the non-obese group. Pearson’s correlation analysis showed a significant (r = -0.9) negative correlation between BMI and serum magnesium in postmenopausal women. Conclusions: Serum magnesium was lower in obese postmenopausal women as compared to that in non-obese postmenopausal women. Serum magnesium was negatively correlated with BMI. Magnesium supplementation may be useful in prevention of obesity after menopause.